Adapting the Golden Age Crime Fiction Genre in the “Kain Songket Mysteries” Series - Philip, Susan (Department of English, Faculty of Arts and Social Sciences, University of Malaya, 2018)
In this paper, I examine the way in which the conventions of the Golden Age genre of crime fiction have been adapted to a completely different socio-cultural setting in Barbara Ismail’s “Kain Songket Mysteries”. The Golden Age novels of Agatha Christie and Dorothy Sayers offer neat solutions to their mysteries, implying an unproblematic return to the right path; at the same time, the conventions of the form underline the corruption and danger hidden within these apparently perfect societies. Similarly, Ismail focuses on life in a village in Kelantan, Malaysia, in the 1970s, offering her readers a chance to revel in the gracious social order of the time, while creating inevitable juxtapositions with the ways in which that society has changed in the present. Ismail’s seemingly rose-tinted vision of the Kelantan of forty years ago develops as the novel progresses, culminating in a rather bleak assessment of where that society is heading.